Assessment center for senior engineering students: In-person and virtual approaches. (July 2021) - Lara-Prieto, Vianney; Niño-Juárez, Elvira
Highlights: Senior students interact in multidisciplinary teams to solve a real-life challenge. Increased students' employability given evaluators' constructive feedback. Companies identify potential talent and strengthen collaboration with the university. Comparison between in-person and virtual Assessment Center approaches. Abstract: An Assessment Center with senior Mechatronics and Biomedical Engineering students was established to strengthen and measure transversal competencies before graduation. Students solved a relevant case during this standardized exercise while internal professors and external evaluators (disciplinary experts and human resources staff from different companies) observed the students' performance. Finally, each evaluator had the opportunity to ask specific questions to the students and give them general feedback. This exercise resulted in an excellent opportunity to showcase our students' competencies with the companies and improve their employability, preparing graduates to be hired soon after graduation. This project describes the case study of the Assessment Center, its evaluation instruments, and results. The study also compares the in-person and virtual (given the Covid-19 pandemic) approaches of the Assessment Center, discussing the potential of web-based technologies as collaboration tools. Graphical abstract: Image, graphical abstract